The isolation and synthesis of a novel benzofuran compound from Tephrosia purpurea, and the synthesis of several related derivatives, which suppress histamine H1 receptor gene expression. Issue 21 (1st November 2015) - Shill, Manik Chandra; Das, Asish Kumar; Itou, Tomohiro; Karmakar, Sanmoy; Mukherjee, Pulok K.; Mizuguchi, Hiroyuki; Kashiwada, Yoshiki; Fukui, Hiroyuki; Nemoto, Hisao
Graphical abstract: Abstract: A novel naturally occurring compound with a benzofuran skeleton was isolated from a plant, Tephrosia purpurea collected in Bangladesh. The chemical synthesis of this compound confirmed its structure, and preliminary biological results showed its suppressive activity towards histamine H1 gene expression. One isomer and four derivatives were also synthesized, and their suppression activity was investigated. Although only small quantities of this compound can be isolated from its natural source, a 10 g scale synthesis was demonstrated by the newly developed method.